Discerning interface atomistic structure by phase contrast in STEM: The equilibrated Ni-YSZ interface. (1st August 2018) - Nahor, Hadar; Kauffmann, Yaron; Lazar, Sorin; Shilo, Doron; Kaplan, Wayne D.
Abstract: Equilibrated interfaces between Ni and yttrium stabilized zirconia (YSZ) were formed by solid-state dewetting of thin Ni films on the (111) surface of YSZ single crystals at 1350 °C and an oxygen partial pressure of P(O2 ) = 10 −20  atm. The atomistic structure of the equilibrated solid-solid Ni [ 1 ¯ 10 ] 111 ∥ YSZ [ 1 1 ¯ 0 ] 111 interface was determined by monochromated and aberration-corrected scanning transmission electron microscopy, using different techniques. It was found that due to the large lattice mismatch between Ni and YSZ the interface reconstructs, and adopts a unique structure which consists of a high density of misfit dislocations. However, despite the large lattice mismatch, this interface is not incoherent. The interface was confirmed to be cation terminated, which is probably due to the low oxygen partial pressure used to reach equilibrium. Graphical abstract: Image 1